Melt blending of poly(lactic acid) with biomedically relevant polyurethanes to improve mechanical performance - Stefan Oschatz; Selina Schultz; Nicklas Fiedler; Volkmar Senz; Klaus-Peter Schmitz; Niels Grabow; Daniela Koper (Heliyon, 2024)
Minimally invasive surgery procedures are of utmost relevance in clinical practice. However, the associated mechanical stress on the material poses a challenge for new implant developments. In particular PLLA, one of the most widely used polymeric biomaterials, is limited in its application due to its high brittleness and low elasticity. In this context, blending is a conventional method of improving the performance of polymer materials. However, in implant applications and development, material selection is usually limited to the use of medical grade polymers. The focus of this work was to investigate the extent to which blending poly-l-lactide (PLLA) with low contents of a selection of five commercially available medical grade polyurethanes leads to enhanced material properties. The materials obtained by melt blending were characterized in terms of their morphology and thermal properties, and the mechanical performance of the blends was evaluated taking into account physiological conditions. From these data, we found that mixing PLLA with Pellethane 80A is a promising approach to improve the material's performance, particularly for stent applications. It was found that PLLA/Pellethane blend with 10% polyurethane exhibits considerable plastic deformation before fracture, while pure PLLA fractures with almost no deformation. Furthermore, the addition of Pellethane only leads to a moderate reduction in elongation at yield and yield stress. In addition, dynamic mechanical analysis for three different PLLA/Pellethane ratios was performed to investigate thermally induced shape retention and shape recovery of the blends.